Nanotechnology and its legal and social implications - Karim, M.E. (2014)
Nanotechnology is the next industrial revolution after internet and the wave of the future. Countries around the world have been investing huge and thousands of consumer products containing nanomaterial are already in the market. However, industries are apparently more inclined to generate revenue ignoring societal concerns, which may have serious negative impact. This paper aims at reviewing the legal and societal aspects of nanotechnology, and shares an overview of present trend and recent developments around the world. The paper will argue that unless the society is included in the whole process, the ultimate purpose of generating money will be frustrated.